PEMBERDAYAAN KADER POSYANDU MAWAR GRAND RESIDENCE KELURAHAN CIJENGKOL KECAMATAN SETU BEKASI DALAM UPAYA PENGELOLAAN DATA TUMBUH KEMBANG BALITA - Timorora Sandha Perdhana; Djuni Thamrin (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2023)
The importance of monitoring and checking children's health at the golden age of children in the age range of 0-5 in terms of the adequacy of nutritious food to produce a healthy, smart and productive generation of children. Through the Posyandu program, activities are carried out regularly every month to monitor height measurement, weight, immunization and vitamin administration to children. The key to the success of Posyandu is the existence of Posyandu cadres. There are approximately eight cadres at posyandu Mawar Grand Residence. As an effort to increase knowledge in posyandu cadres, the implementation team initiated training activities related to a comprehensive understanding of child growth and development which should be an important role in controlling child development at an early age. In addition, as an effort to increase understanding of technology for Posyandu cadres and as a solution to overcome problems related to unstructured data recording, a website-based Posyandu data recording application was made.